Harvesting of invasive woody vegetation (Eucalyptus lehmanii, Leptospermum laevigatum, Acacia cyclops) as energy feedstock in the Cape Agulhas Plain of South Africa - Kitenge, Emile Museu (Stellenbosch : Stellenbosch University, 2011)
Thesis (MFor)--Stellenbosch University, 2011.